2022
DOI: 10.1186/s41927-022-00303-w
|View full text |Cite
|
Sign up to set email alerts
|

Who stop telemonitoring disease activity and who adhere: a prospective cohort study of patients with inflammatory arthritis

Abstract: Background The use of frequent electronic patient reported outcome measures (ePRO’s) enables monitoring disease activity at a distance (telemonitoring) in patients with inflammatory arthritis. However, telemonitoring studies report declining long-term adherence to reporting ePRO’s, which may oppose the benefits of telemonitoring. Therefore, the objective was to investigate what factors are associated with (non-)adherence to telemonitoring with a weekly ePRO in patients with inflammatory arthrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…All participants that participated in the Self-Monitoring of Rheumatoid Arthritis (SEMORA) trial (n = 49) or the Digital Cohort of Inflammatory Rheumatic Diseases (DICODE) study (n = 220), were invited by email to participate in the FGDs. The main results of both trials have been published elsewhere [16,17]. In short, both studies included patients over 18 years old, who were owner of a smartphone and able to read Dutch.…”
Section: Focus Group Discussion Samplementioning
confidence: 99%
See 3 more Smart Citations
“…All participants that participated in the Self-Monitoring of Rheumatoid Arthritis (SEMORA) trial (n = 49) or the Digital Cohort of Inflammatory Rheumatic Diseases (DICODE) study (n = 220), were invited by email to participate in the FGDs. The main results of both trials have been published elsewhere [16,17]. In short, both studies included patients over 18 years old, who were owner of a smartphone and able to read Dutch.…”
Section: Focus Group Discussion Samplementioning
confidence: 99%
“…A limitation of this study was that selection bias may have occurred, which could influence the generalizability. Selection bias is often present in telemonitoring studies in rheumatology, and is also likely present in this study as the participants were a subset of previously performed telemonitoring studies, that both included a relatively high percentage of patients with tertiary education [5,16,17]. This is highlighted by the seven patients who did not want to participate after changing the FGD to online.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite these promising results in clinical trials, ePROs have not yet found broad application in routine clinical practice, mainly due to a low completion rate by patients [ 6 ]. Recent trials showed a decreasing completion of ePROs over time, down to 40% after six months [ 3 , 7 , 8 ]. To date, only a little evidence is available on which patient factors are associated with a lower or higher ePRO response rate.…”
Section: Introductionmentioning
confidence: 99%